PERANCANGAN SISTEM MONITORING LISTRIK 3 PHASA BERBASIS INTERNET OF THINNGS (IOT) - Syarif Ishak Alkadri; Akhdiyatul Akhdiyatul (Electrical Network Systems and Sources, 2023)
ABSTRACT The electrical system is an important component in modern infrastructure, because almost all devices used in human activities today use electricity as a resource. To maintain the continuity of these activities, a system is needed that can monitor electrical conditions in real time in order to prevent bigger problems from occurring in the electrical system. This monitoring system uses the PZEM-004T to measure voltage, current, and frequency. NodeMCU ESP8266 to help display data such as, Voltage, Current, and Frequency on I2C and Blynk LCDs. I2C LCD to display Voltage, Current and Frequency. And Blynk to display Voltage, Current and Frequency. The results of the tests that have been carried out have an average error value of 0.0012% for voltage and 0.28% for current. Where the average error value in each test is below the tolerance value stated in the PZEM-004T sensor specifications, which is 0.5%. Keywords: Monitoring, Voltage, Current, Frequency, Blynk.